Detectors and Imaging Devices: Infrared, Focal Plane, Single Photon 2010
DOI: 10.1117/12.876144
|View full text |Cite
|
Sign up to set email alerts
|

Long-range depth imaging using time-correlated single-photon counting

Abstract: Active, three-dimensional long-range imaging has varied applications in a number of disciplines, including manufacturing, environmental sensing and defence. Common constraints often include low average and peak illumination powers to ensure eye-safety, making the potentially high sensitivity of the single-photon counting technique a distinct advantage. We present a scanning time-of-flight imager based on high repetition-rate (>MHz) pulsed illumination and a silicon single-photon detector. In advanced photon-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…The inherent jitter of system is contributed by each component of the TCSPC system, such as the pulsed laser, the photon counting module and the signal processing module and so on. In our system, a commercially sophisticated photon counting module (SPCM-AQRH-14, Perkin Elmer) has been adopted [12], whose jitter cannot be changed and improved in our system. However, the overall jitter generated by pulsed laser and signal processing module, whose histogram is shown in Fig.7, can been measured and improved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inherent jitter of system is contributed by each component of the TCSPC system, such as the pulsed laser, the photon counting module and the signal processing module and so on. In our system, a commercially sophisticated photon counting module (SPCM-AQRH-14, Perkin Elmer) has been adopted [12], whose jitter cannot be changed and improved in our system. However, the overall jitter generated by pulsed laser and signal processing module, whose histogram is shown in Fig.7, can been measured and improved.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the picosecond jitter will result in the precision of centimeters. In previous research, construction of a TCSPC based TOF laser range finder has been reported in various applications [11][12][13][14]. However, the impact of SNR and jitter on the performance of this type of system is under-researched.…”
Section: Introductionmentioning
confidence: 96%
“…η atm denotes laser's transmission efficiency through the atmosphere, which can be expressed as a function of the target range R and the atmospheric attenuation factor μ a (i.e., η atm = e −μ a R ). η sys denotes receiver optical system's efficiency and it is measured as 0.07 using the method in reference [40]. The value of η sys is not very high for the reason of optical elements' attenuation (i.e., band pass filter, objective lens, eyepiece and fiber), fiber coupling losses and possible misalignment of the optical system.…”
Section: Rm Sementioning
confidence: 99%